Efeito anti-inflamatório e antirreabsortivo da terapia probiótica com kefir de leite no desenvolvimento da periodontite induzida por ligadura em ratos - Vieira, Lorena Vasconcelos (2020)
Periodontitis is characterized by a chronic inflammatory process that leads to the destruction of both soft and hard tissues that support the dental units. It affects 35% to 60% of the adult population, and its most severe form affects 5% to 10% of the world population. In recent years, the search for new therapeutic alternatives is increasing, and probiotics have assumed a prominent role in this process. Within this context, there is kefir, composed of a complex microbiological diversity. The aim of the present study was to evaluate the anti-inflammatory and anti-resorptive effect of milk kefir (MK) on experimental periodontitis in rats. Thus, Wistar rats were divided into the following groups (n = 6): C (Control, animals without periodontitis and no administration of MK); EP (experimental periodontitis); group K1 (animals that received MK with one day of fermentation); K1 + EP (animals with EP using MK with one day of fermentation); K4 (animals without EP using MK with four days of fermentation) and K4 + EP (animals with EP using MK with four days of fermentation). Kefir was administered by gavage (0.7 ml per day) 28 days before EP induction and during the disease development period (11 days), totaling 39 days of treatment. On day 28, in the EP groups, it was induced by a ligature around the left upper second molar. The animals with EP and using MK were euthanized on day 39. The hemimaxyls were removed and the following parameters were evaluated: (1) micro-Raman spectroscopy analysis of the presence of L. kefiri and inflammation; (2) histomorphometric analysis to quantify bone loss in furcation area; and (3) immunohistochemistry for cytokines IL-6, TNF-a and IL-Ib in the periodontal ligament. Micro-Raman analysis showed that four days of fermentation KL has a higher intensity spectrum of L.kefiri, as well as the administration of this probiotic reduced the intensity of the inflammation spectrum when compared to one day fermentation MK. It was observed that the animals from the K4 + EP group showed significant reduction of bone loss, as well as a lower IL-6, TNF-a and IL-Ib immunoexpression, when compared to EP groups. We conclude that 4 days of fermentation MK has anti-inflammatory and anti-resorptive effect on EP in rats and that these effects are related to a higher presence of L. kefiri.